Evaluation of Pressure Elements in the Penalty Kicks - Şaban Tuğlu, Egemen Ermiş, Necati Alp Erilli (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A penalty kick in football is one of the most important rules that directly affect the score of the match. Penalty kicks have always been the focus of attention in terms of both the result and the shot. Aim: The aim of this study is to determine whether the one who takes the penalty or saves the penalty is more effective and to determine whether the players who use the penalty show a tendency in a certain direction. Methods: In this study, a detailed analysis of penalty shootouts with the 10-year data of the Turkish Super League was made. SPSS.22 package program was used in statistical analyses. Analyses of penalty kicks were compared with the Chi-square test and the level of significance was taken as 0,05 in all tests. Results: According to the results of the analysis, goalkeepers guessed correctly 46% of the direction where the ball passed in all penalties (r=0.74; p=0.000). 52% of left-footed penalty takers shot to the left, and 46.9% of right-footed penalty takers to the right. There was no statistical difference between the direction where the ball was thrown, and the foot used by the penalty kicker (p>0.05). Conclusion: In the analysis made with 10-year data, it has been determined that the players do not tend to a certain direction when using penalties.